2011
DOI: 10.7557/2.31.2.1996
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial lichen response to partial cutting in lodgepole pine forests on caribou winter range in west-central British Columbia

Abstract: In west-central British Columbia, terrestrial lichens located in older, lodgepole pine (Pinus contorta) forests are important winter forage for woodland caribou (Rangifer tarandus caribou). Clearcut harvesting effectively removes winter forage habitat for decades, so management approaches based on partial cutting were designed to maintain continuous lichen-bearing habitat for caribou. This study tested a group selection system, based on removal of 33% of the forest every 80 years in small openings (15 m diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…He observed that environmental conditions under piles and at pile edges were moderated, and appeared to provide suitable microenvironments for lichens, whereas lichens present in road-side delimbed sites without cover often appeared to be suffering damage from exposure. Waterhouse et al (2011) observed that slash on the ground and suspended low above the ground adversely affected lichens, but high suspended slash and areas adjacent to slash piles may provide refugia for lichens. An important point raised by Waterhouse et al (2011) was that whole-tree (WT) and stem-only (SO) harvesting systems have the potential of affecting lichens differently.…”
Section: Interactions With Understory Shrubs and Woody Debrismentioning
confidence: 98%
See 3 more Smart Citations
“…He observed that environmental conditions under piles and at pile edges were moderated, and appeared to provide suitable microenvironments for lichens, whereas lichens present in road-side delimbed sites without cover often appeared to be suffering damage from exposure. Waterhouse et al (2011) observed that slash on the ground and suspended low above the ground adversely affected lichens, but high suspended slash and areas adjacent to slash piles may provide refugia for lichens. An important point raised by Waterhouse et al (2011) was that whole-tree (WT) and stem-only (SO) harvesting systems have the potential of affecting lichens differently.…”
Section: Interactions With Understory Shrubs and Woody Debrismentioning
confidence: 98%
“…Waterhouse et al (2011) observed that slash on the ground and suspended low above the ground adversely affected lichens, but high suspended slash and areas adjacent to slash piles may provide refugia for lichens. An important point raised by Waterhouse et al (2011) was that whole-tree (WT) and stem-only (SO) harvesting systems have the potential of affecting lichens differently. Whole tree skidding is likely to cause more damage to the lichen mat than skidding of delimbed stems, and results in roadside processing areas that are severely disturbed.…”
Section: Interactions With Understory Shrubs and Woody Debrismentioning
confidence: 98%
See 2 more Smart Citations
“…Biomass and cover of dwarf-shrubs and most mosses decrease due to disturbance, while lichens, forbs and graminoids are often regenerating abundantly in sites disturbed by fire and/or clearcutting (Fig. 3;Foster 1985;Shevtsova et al 1995;Schimmel and Granström 1996;NguyenXuan et al 2000;Parlane et al 2006;Waterhouse et al 2011;Turtiainen et al 2013;Johnson et. al.…”
Section: Joint Soil-vegetation Patterns Across the Sitesmentioning
confidence: 99%